A Neutrosophic Triplet Field Model for Assessing Transitional Aesthetic Zones in Computer-Aided Art Design Systems - Yuxiang Wang (Neutrosophic Sets and Systems)
Computer-Aided Art Design (CAAD) systems often produce outputs with complex visual transitions that are difficult to evaluate using binary or crisp metrics. Traditional quality assessment models fail to represent the uncertainty and partial aesthetic impact present in transitional regions areas between visually pleasing and visually rejected zones. This paper proposes a novel neutrosophic triplet field model that quantifies the aesthetic quality of design outputs using three independent components: degree of visual truth (T), perceptual indeterminacy (I), and aesthetic failure (F). The model draws on principles from the Neutrosophic Magnetic Field to define spatial zones of influence and incorporates a partially-observed field response inspired by Neutrosophic Quantum Theory. Mathematical functions define each component across a design surface, and several equations are derived to compute zone-specific values. A fully calculated case study on a discretized design space demonstrates the model's ability to detect and differentiate visually ambiguous zones. Results show the importance of transitional zones where indeterminacy peaks as key contributors to nuanced aesthetic perception. This model offers a rigorous, quantifiable, and human-relevant framework for analyzing artistic quality in CAAD systems.